In situ local imaging and analysis of impregnation during liquid moulding of composite materials using synchrotron radiation computed laminography. (20th October 2021) - Castro, J.; Sket, F.; Helfen, L.; González, C.
Abstract: Analysis of the impregnation process during injection experiments in fibre-reinforced polymer composites has been carried out via a three-dimensional in-situ imaging method, namely Synchrotron Radiation Computed Laminography (SR-CL). A resin transfer moulding device was designed to perform injection experiments at different flow rates while, at the same time, the evolution of the flow front was inspected by SR-CL. Injections with flow rates of 50  μ L/min and 300  μ L/min in plain woven E-glass fabrics were carried out, resulting in small capillary number fluid propagation with capillary forces dominant over viscous ones. Intratow and intertow voids were accurately segmented by using a machine learning algorithm that enabled the direct measurement of their time and spatial distribution from the raw XCT volumes. The saturation evolution, void content, shape and spatial distribution quantification are reported. Intratow void formation and transport mechanisms were accurately described, in particular those related with large void splitting including the subsequent flow dragging. Advantages and limitations of the use of SR-CL for the analysis of the impregnation process of dry preforms in liquid moulding are discussed in detail, and in particular, those aspects related with the time acquisition limitations. Graphical abstract: Image 1